KOREA: KLUCZ DALEKIEGO WSCHODU (1905) AND WACŁAW SIEROSZEWSKI’S VIEW OF KOREA - LEE, Yeong-Mi (International Journal of Korean Humanities and Social Sciences, 2017)
The aim of this paper is to review Wacław C. Sieroszewski’s (1858-1945) view of Korea. He, well-known Polish writer, traveled to Korea, i. e., Daehan Empire (大韓帝國), in fall of 1903, and published Korea: Klucz Dalekiego Wschodu (1905). Considering that most of travelogues of Korea were written by American, British, French, and German, so-called “Western powers,” KKDW was a pretty valuable book. The author believes that Western view of Korea was notably changed around the late eighteenth century. In the seventeenth and eighteenth centuries, Europeans did not ignore or belittle Korea and Korean. They regarded Korea as a rich and well-systemized country, and Korean as an intelligent nation, although they had very little knowledge of Korea. On the other hand, generally speaking, they degraded Korea and Korean in the nineteenth and early twentieth centuries, and Sieroszewski was one of them. Poland was one of the weakest countries in Europe, but his view was not different from that of American, British, French, and German authors. Sieroszewski was favorably impressed by Japan before he came to Korea in October, 1903, and, as a result, he constantly compared Korea and Japan. He even wrote that Japan was better than Europe in some ways. He truly believed that Japan was the only country to carry out a desirable reform for Korea. Meanwhile, he never approved the Russia’s imperialist ambition for Korea. He considered Japan as an agent of the West. In conclusion, his idea of Korea and the East was quite similar to that of other contemporary Western travelers.